TTR gene silencing therapy in post liver transplant hereditary ATTR amyloidosis patients. (1st October 2020) - Moshe-Lilie, Orly; Dimitrova, Diana; Heitner, Stephen B.; Brannagan, Thomas H.; Zivkovic, Sasha; Hanna, Mazen; Masri, Ahmad; Polydefkis, Michael; Berk, John L.; Gertz, Morie A.; Karam, Chafic
Abstract: Objective: Patients with hereditary transthyretin (TTR) amyloidosis (hATTR) often experience disease progression after orthotopic liver transplant (POLT) due in part to wild type ATTR amyloid deposition. The management strategy is not defined. We propose that TTR gene silencing with an antisense oligonucleotide or a small interfering ribonucleic acid may be a treatment for these patients. Methods: We reviewed the charts of hATTR patients POLT treated with a TTR gene silencing agent at 7 different Amyloid Clinics between 2018–2020. Results: Nine hATTR patients with POLT were treated with TTR gene silencing therapy (Inotersen). The median age was 61 years. The median time from OLT to initiation of TTR gene silencing therapy was 7.5 years. The median duration of therapy was 12 months. Neuropathy impairment score remained stable or improved in all patients. Five patients stopped treatment: 3 because of thrombocytopenia, 2 because of reversible liver rejection. Three patients who discontinued treatment subsequently experienced worsening of their neuropathy. Conclusion: TTR gene silencing therapy in hATTR patients with POLT could be a treatment option. Vigilant monitoring of renal, liver and bone marrow functions is necessary because of frequent complications. Further studies are needed to determine efficacy.